دراسة العلاقة بين الأداء التنظيمي ونجاح المشروعات من خلال أثر الثقافة التنظيمية دراسة حالة على مجموعة ابن لادن للمقاولات بالمملكة العربية السعودية - شريف إبراهيم عبده دسوقي
Projects are often used as one of the most substantial means of achieving the country's strategic plan. As countries work to invent ideas and projects through which they can achieve growth and development plans that respond to the needs and aspirations of all segments of society, The success achieved in implementing these various projects represents a significant criterion for success in implementing strategic plans. This constitutes a great challenge for companies and departments to implement their projects, To bring about a qualitative leap in the performance of their administrative department, which raises its ability to achieve success in the implementation of projects, The successful implementation of projects by companies means the success of a significant part of the countries plan, and its failure to implement projects will result in unfavourable effects on the countries development plans, Therefore, the importance of ensuring the ability of companies to implement projects successfully emerged. This study seeks to clarify the importance of the relationship between organizational performance efficiency on the success of companies in implementing projects using organizational culture as a mediating variable. As the Bin Laden Group in the Kingdom of Saudi Arabia is one of the enormous contracting companies in Saudi Arabia and the Arab world, with revenues estimated at five billion dollars, Therefore, the project management employees in the Bin Laden Group were selected as a practical case through which the effect of the study variables can be measured. To achieve the objectives of the study, the quantitative approach, description, analysis, and a survey list developed by the study were relied on to collect the primary data that served the purpose of the study. Through the Cronbach alpha scale, the stability of the measures of the study variables was confirmed, using the multiple regression analysis methods, and the structural equation modelling (SEM) method, To test the hypotheses and model of the study. The study reached many results, including that there is a direct positive statistical relationship between the efficiency of organizational performance and the success of projects in contracting companies in the Kingdom of Saudi Arabia. The results also showed an effect of the mediating organizational culture variable in the relationship between the efficiency of organizational performance and the success of projects. The study recommended the need to extend focus and investment in raising the efficiency of organizational performance by creating and developing an inspiring and creative organizational culture in producing and employing the talents and capabilities of work teams in all companies operating in the Kingdom of Saudi Arabia because they influence the success of companies in implementing projects.